2021
DOI: 10.4149/neo_2021_210104n8
|View full text |Cite
|
Sign up to set email alerts
|

CD150 and CD180 are negative regulators of IL-10 expression and secretion in chronic lymphocytic leukemia B cells

Abstract: Chronic lymphocytic leukemia (CLL) is a strikingly heterogeneous disease both at the molecular level and clinical disease course. The key proliferation and survival signals malignant B cells obtain within lymph nodes or bone marrow. Moreover, CLL B cells and tumor microenvironment dynamically co-evolve organizing inflammatory and immunosuppressive microenvironment by direct contact with surrounding cells and secretion of cytokines, growth factors, or extracellular vesicles. Finding a way to weaken obtaining by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…NLR receptor genes recognize pathogenic microorganisms that invade the cell and regulate the innate immune response of the body against pathogenic microorganisms [ 41 ]. SLAMF1 genes act as negative regulators of type I interferon production and NF-κB activation, and SLAMF1 genes knockout mice showed reduced clearance of Gram-negative bacteria [ 42 ], indicating that the SLAMF1 gene has a very important role in immune regulation and disease prevention and control. In this study, we examined the expression of PRRs and cytokines in the cellular inflammatory pathway after SLAMF1 inhibited PRRSV replication and revealed that SLAMF1 could exert antiviral effects and suppress the level of virus-induced inflammation in Marc-145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…NLR receptor genes recognize pathogenic microorganisms that invade the cell and regulate the innate immune response of the body against pathogenic microorganisms [ 41 ]. SLAMF1 genes act as negative regulators of type I interferon production and NF-κB activation, and SLAMF1 genes knockout mice showed reduced clearance of Gram-negative bacteria [ 42 ], indicating that the SLAMF1 gene has a very important role in immune regulation and disease prevention and control. In this study, we examined the expression of PRRs and cytokines in the cellular inflammatory pathway after SLAMF1 inhibited PRRSV replication and revealed that SLAMF1 could exert antiviral effects and suppress the level of virus-induced inflammation in Marc-145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…One such notable receptor, SLAMF1, serves as a suppressor of IL-10 expression and release on the B-CLL cell surface. There is a documented correlation between SLAMF1's presence and improved clinical prognosis in CLL patients [26]. Notably, an increased expression of both SLAMF1 and SLAMF7 emerges as a positive prognostic sign.…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 95%
“…Several studies have expanded current knowledge on SLAMF1 in the pathophysiology of CLL and lymphoma (12,85,87,(118)(119)(120). A study has demonstrated that SLAMF1 acts as a negative regulator of IL-10 expression and secretion on the surface of B cell CLL and is associated with favorable clinical outcomes (12).…”
Section: Slam Molecules Have a Role In Tumor Immunity And Cancer Immu...mentioning
confidence: 99%
“…Previous studies have reported the role of SLAMs in tumor immunity in a variety of cancers, including chronic lymphocytic leukemia (CLL) (11), lymphoma (12), multiple myeloma (MM) (13), acute myeloid leukemia (AML) (14), hepatocellular carcinoma (HCC) (15), head and neck squamous cell carcinoma (HNSCC) (16), pancreas (17), lung (17), and melanoma (18). Anti-CTLA-4 and anti-PD-1 mAbs have been incredibly effective.…”
Section: Introductionmentioning
confidence: 99%